Chemical composition as an indicator for evaluating heated whey protein isolate (WPI) and sugar beet pectin (SBP) systems to stabilize O/W emulsions. (15th November 2020) - Xiao, Yingping; Qi, Phoebe X.; Wickham, Edward D.
Highlights: Solution heating with SBP at all levels averted the losses of -SH and –NH2 in WPI. Changes in chemical composition were indicative of productive conjugation reaction. Conjugates formed between WPI and SBP were critical for improved emulsion stability. Electrostatic interaction contributed to the improved emulsion stability at pH 3.2. Adverse conditions (unbalanced ratios, neutral pH) affected the emulsion negatively. Abstract: We investigated changes in the chemical composition of WPI as a result of heating (60 °C, 72 h) with SBP in solution (pH 6.75). The concentration of WPI was kept at a constant (3%), whereas the level of SBP was varied at 1, 1.5, and 3%. The reaction products were examined using the Ellman's reagent, ninhydrin assay, and gel electrophoresis. The results demonstrated that the losses of the free sulfhydryl (-SH) and primary amine (–NH2 ) contents in WPI were less severe compared to those occurring in the dry-state at similar conditions (mass ratio, temperature, and reaction duration). The mixtures were used as emulsifiers in an O/W emulsion system at pH 3.20 and 6.75 and showed an improved ability to stabilize the average size of the droplets than WPI alone at acidic pH. The mixtures at higher levels of SBP, ≥ 1.5%, however, adversely affected the emulsion stability at neutral pH.